2011
DOI: 10.2118/140253-pa
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Hydraulic-Fracture-Network Propagation in a Naturally Fractured Formation

Abstract: Summary Hydraulic fracturing in shale-gas reservoirs has often resulted in complex-fracture-network growth, as evidenced by microseismic monitoring. The nature and degree of fracture complexity must be understood clearly to optimize stimulation design and completion strategy. Unfortunately, the existing single-planar-fracture models used in the industry today are not able to simulate complex fracture networks. A new hydraulic-fracture model is developed to simulate complex-fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
128
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(132 citation statements)
references
References 25 publications
1
128
0
3
Order By: Relevance
“…In particular, we demonstrated that the stress contrast in the infill region reaches its lowest value exactly at the onset time of stress reversal halfway between the producing wells. Weng et al (2011) showed that interactions between hydraulic and natural fractures are largely influenced by the stress regime in which the induced fracture propagates. If the difference between minimum and maximum horizontal stresses is small, an induced fracture will have a larger tendency to branch-out when intersecting natural fractures, thus forming more complex fracture networks.…”
Section: Timing Of Infill Operationsmentioning
confidence: 99%
“…In particular, we demonstrated that the stress contrast in the infill region reaches its lowest value exactly at the onset time of stress reversal halfway between the producing wells. Weng et al (2011) showed that interactions between hydraulic and natural fractures are largely influenced by the stress regime in which the induced fracture propagates. If the difference between minimum and maximum horizontal stresses is small, an induced fracture will have a larger tendency to branch-out when intersecting natural fractures, thus forming more complex fracture networks.…”
Section: Timing Of Infill Operationsmentioning
confidence: 99%
“…The interaction between a hydraulic fracture (HF) and natural fracture (NF) can lead to the propagation of a fracture network (Jang et al 2015;Cai et al 2017), which is also influenced by heterogeneity of reservoir layers, irregular distribution of natural fractures and especially the in situ stress field (Olson 2008;Olson and Taleghani 2009). Weng et al (2011) and Weng (2015) developed an unconventional fracture model (UFM) and considered stress field, the orientation of the NF and rock deformation, which is very powerful to describe the hydraulic fracture propagation using an unstructured grid. On the other hand, the wiremesh model (Xu et al 2009(Xu et al , 2010Meyer and Bazan 2011) utilizes two orthogonal sets of planar elements to represent the area of the fracture network and stimulated reservoir volume (SRV), which is simple but effective for network modeling (Weng et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Weng et al (2011) and Weng (2015) developed an unconventional fracture model (UFM) and considered stress field, the orientation of the NF and rock deformation, which is very powerful to describe the hydraulic fracture propagation using an unstructured grid. On the other hand, the wiremesh model (Xu et al 2009(Xu et al , 2010Meyer and Bazan 2011) utilizes two orthogonal sets of planar elements to represent the area of the fracture network and stimulated reservoir volume (SRV), which is simple but effective for network modeling (Weng et al 2011). Fracture spacing, the complexity of the fracture network and the grid's properties are considered during the hydraulic fracture propagation.…”
Section: Introductionmentioning
confidence: 99%
“…There are some mathematic models to present the complex shale fracture morphological characteristics. For example, Weng et al (2011) presented the Unconventional Fracture Model (UFM), which can simulate complex-fracture-network propagation in a formation with preexisting natural fractures. Wenyue Xu et al (2009) put forward Wire-mesh model, which was fully constrained when accounting for mechanical interactions between injected fluid and fracture walls and among nearby fractures and when satisfying observation data including wellbore pressure and microseismic event distribution.…”
Section: Introductionmentioning
confidence: 99%